Gotong Royong Economy: Strengthening Islamic Values Through Local Traditions - Qosim, Nanang; Ansori, Ansori; Masduqie, Muhammad Hamdan Ali (Proceedings of Annual Conference for Muslim Scholars, 2024)
This article examines the concept of gotong royong economy as a manifestation of Islamic values strengthened through Indonesian local traditions. This research uses a qualitative approach with literature study and content analysis methods to explore the intersection between Islamic economic teachings and the practice of gotong royong in Indonesian society. The results of the analysis reveal that the implementation of a gotong royong economy can strengthen social cohesion, improve shared prosperity, and create a more just and inclusive economic system. The article also identifies some challenges in implementing the gotong royong economic model in the modern era, and offers recommendations to actualize this concept in the context of contemporary economic development. In conclusion, the gotong royong economy offers a unique paradigm in combining Islamic values with local wisdom, providing a strong foundation for the development of an economic system that is not only efficient, but also harmonious with Indonesia's spiritual and cultural values